Association between COVID-19 Vaccination (ChAdOx1-S) and Thromboembolic, Thrombocytopenic, Hemorrhagic Events: A Systematic Review and Meta-analysis of Analytical Epidemiological Studies. - Vaman, Raman S.; Kumar, Muthusamy S.; Jeyashree, Kathiresan; Periasami, Ashok; Abdulkader, Rizwan S.; Murhekar, Manoj (Indian Journal of Community Medicine)
We conducted a systematic review of analytical epidemiological studies to assess the association between ChAdOx1-S vaccination and thromboembolic, thrombocytopenic, and hemorrhagic events. We searched Medline, Embase, Google Scholar, WHO-COVID-19 database, and medRxiv for studies evaluating the association between ChAdOx1-S and vascular events. Primary outcomes of interest were cerebral venous sinus thrombosis, peripheral venous thrombosis (PVT), and thrombocytopenia. Two independent reviewers screened for eligible studies, extracted data, and assessed the risk of bias. The DerSimonian-Laird random effects model was used to pool the incidence rate ratios (IRRs) separately for the first and second doses. Heterogeneity was assessed using I2 statistics. Twenty studies were included, of which 11 were self-controlled case series, and nine were cohort studies (254 million participants). Pooling of 17 studies showed a higher risk of cerebrovascular thrombosis (IRR = 3.5, 95% CI = 2.2-5.4, I² = 79%), PVT (IRR = 2.0, 95% CI = 1.1-3.5, I² = 95%) and thrombocytopenia (IRR = 1.6, 95% CI = 1.4-1.9, I² = 93%) among those who received ChAdOx1-S vaccination as compared to controls. No increased risk was seen after the second dose or for secondary outcomes. There is moderate-to-high certainty of the evidence for the increased risk of cerebral venous sinus thrombosis, PVT, and thrombocytopenia following the first dose of the ChAdOx1-S vaccine. Systematic Review Registration: PROSPERO CRD42022372768.